World Cultural Stage and Retranslation of Local Tradition - Sugiharto, Ignatius Bambang; Tedjoworo, Hadrianus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2015)
Culture may transgress geopolitical boundaries. these days, especially when the survival of a certain community is under the threat of global political power, the need to overemphasize cultural uniqueness arises more strongly. Tradition is ambiguous and multi-interpretable, depending on the frame of interpretation, interest, power, and above all, on the dialectical encounter of ‘translation’: only in relation with something other and different, particular aspect of the tradition comes up. More than simply a matter of ‘transmission’, tradition is in fact a process of on-going ‘transformation’ and ‘reinterpretation’. The world becames a huge stage where multiple waves of existence intersect and realize the complexity, ambiguity and subtlety of each other’s world and of their own. In the interaction self-interrogation and mutual self-criticism take place, in which the participating cultures are called into question. In such global stage, cultures would weave and reweave their conceptual networks continually. The world cultural stage today is a never-ending conversation where traditions are not only rearticulated thereby, but also reinvented, and extended to their unpredictable potentialities in terms of new contexts. Culture lives in the conjunctions of our grammar of conversation happening on the stage.